Timing of neuromuscular activiation patterns during flat tennis serve - Pezarat-Correia, P.; Coutinho, C.; Pimentel, P.; Dias, V.; Fernandes, O. (12th Annual Congress of the European College of Sport Science, Jyväskylä, Finland - July 11-14th 2007, 2007)
To characterize the timing of neuromuscular coordination patterns during the tennis serve. We will focus in muscular activities related with the arm and forearm movements during the Acceleration Phase. Methods: 7 portuguese male tennis players performed 5 flat serves to a specific area of the service box. All the players have or had an ATP ranking. A telemetric system was used to record surface EMG in 6 muscles: anterior (AD) and posterior (PD) deltoids, pectoralis major (PM), latissimus dorsi (LD), vastus lateralis (VL) and biceps brachii (BB). The EMG signals were sampled at 1000 Hz, full wave rectified, low pass filtered and normalized using the EMG of the MVC. Each serve was recorded with four high speed video cameras (250Hz) in order to establish the different phases of the action which were used as reference to the EMG analysis. The EMG and kinematic data were synchronized and captured using a SIMI system. Results: The sequence of muscle activation was described by the instant of the activation onset (ONS) and the instant of maximum peak (TmxEMG) related to the beginning of the Acceleration Phase (InAcP) and to the instant of ball contact (BC). The time to peak (ONS-TmxEMG interval) was also measured. All the parameters were determined individually in each serve. The horizontal adductors of the arm were activated during the Backswing Phase and the first half of the Acceleration Phase - AD (ONS 269±90ms, TmxEMG 101±29ms before InAcP, Duration 316±88ms) and PM (ONS 227±30ms before InAcP, Tmx- EMG 1±17ms after InAcP, Duration 321±44ms). The LD (ONS 102±16ms and TmxEMG 44±15ms before BC) presented a short duration burst (148±11ms) with a fast time to peak (53±14ms). The PD peaked during the Follow- Through (67±30ms) but always showed a first peak of activation before BC (ONS 98±16ms and TmxEMG 40±19ms before BC). The VL showed an EMG burst (ONS 49±13ms before InAcP, duration 278±100ms) with two peaks. We can see the first one in the beginning of the Acceleration Phase (0±18ms). The second peak (38±24ms before BC) was coincident with the first TmxEMG of the DP. The BB didn`t show relevant activation during the Acceleration Phase. Conclusions: These preliminary results evidenced the main components of the sequence of muscular coordination during the flat serve. The activation of the horizontal adductors of the arm (AD, PM) during the Backswing prepares the initiation of the Acceleration Phase. In the second half of the Acceleration Phase, the activation of LD is probably fundamental in the kinetic transference from horizontal adduction to the internal rotation of the arm, and the closed relationship in the timing of the activations of VL and PD should be related with the proximal to distal transference from the arm to the forearm. The time parameters we described will be in the future examined in relation to the kinematics of the arm, forearm and to the ball speed to evaluate their specific contributions to serve performance.